A Phytochemical Approach to the Removal of Contaminants from Industrial Dyeing Wastewater (2023)
This study investigates the influence of photoperiod and wastewater concentration on the growth of microalgae and cyanobacteria for the removal of environmentally significant parameters (COD, BOD, Cr, Fe, color, chlorides, nitrogen compounds, and phosphates) from dyeing wastewater. A two-factor central composite design with surface response was employed, involving two algae species (Chlorella and Scenedesmus sp.) and two cyanobacteria species (Hapalosiphon and Oscillatoriasp.). The findings indicated that extended photoperiods (>13 h) and higher wastewater concentrations (70–80% v/v) enhanced biomass production across all strains. However, Hapalosiphon and Chlorellasp. (1.6 and 0.45 g/L) exhibited better tolerance to the wastewater’s high toxicity, resulting in higher biomass concentrations and improved COD and BOD removal by Hapalosiphon sp. (75% and 80%,respectively). Further analysis of the obtained biomass revealed their potential applications. Among the cyanobacteria, Hapalosiphon sp. synthesized the highest concentrations of total proteins and lipids (38% and 28% w/w, respectively), while Oscillatoria sp. displayed a high protein content (42% w/w). In contrast, the algae demonstrated a strong propensity for storing substantial quantities of total carbohydrates (65% and 57% w/w for Scenedesmus and Chlorella sp., respectively). These results signify the feasibility of cultivating photosynthetic microorganisms in industrial dyeing wastewateras a sustainable source of nutrients for targeted metabolite production.